Landscape report on existing financial and logistic services in the agricultural sector in Bangladesh - Bakhtiar, M. Mehrab; Uddin, Mohammad Riad; Shamma, Raisa (International Food Policy Research Institute, 2022)
The economy of Bangladesh is largely defined by the agricultural sector, which is reflected in its yearly GDP contribution of approximately 11% in the past few years (World Bank, 2022). The sector holds po tential for even higher contributions to the economy, provided effective initiatives related to financial inclusion and logistical innovations are implemented. Even during the immense global challenges during to the Covid-19 pandemic, the country’s agricultural sector persisted. Improving on traditional initiatives and practices to address constraints faced by farmers and other agricultural value chain actors will ena ble the sector to expand and benefit new sections of the population, including those most vulnerable such as the poor, women, and youth. Many of the recent innovations in the agricultural sector in Bangladesh have been initiated by ‘AgriTech’ companies/start-ups in the space of financial and logistical services. Financial services are available for both small and large-scale agriculture operations in the country. Besides innovations in fi nancial services, there has been a burgeoning list of logistical services as well. Utilizing this wave of innovations appropriately can help the agricultural sector reach its full potential for success. This report is arranged in the following manner. First section 1 discusses the traditional services in financial and logistic sectors, and then section 2 discusses the existing constraints in both sectors. Sections 3 and 4 go into detail on financial and logistical innovations respectively that aim at addressing the discussed constraints. Both sections 3 and 4 have subsections giving a brief description of organiza tions that are behind these innovations.